Constraint Analysis of Adopters and Non Adopters of Drones in Agriculture in the Warangal District of Telangana in India - Chinthakindi Sreedeepya; D. Kumara Swamy; T. Lavanya; D. Srinivasa Chary (Archives of Current Research International, 2024)
The present study was conducted with an objective to analyse constraints faced by farmers who are using drones, constraints faced by various stakeholders and constraints faced by farmers who are not using drones in agriculture in Warangal district of Telangana, India. Various problems faced by farmers are chosen and Garette’s ranking technique is used to know the major constraints. The major constraints faced by the farmers who are using drones in agriculture are shortage of drone suppliers with a score of 67.95, non uniform coverage with a score of 61.75. the major constraints faced by farmers who are not using drones in agriculture are high labour cost with a score of 73.12, time consuming with a score of 67.55 and the major constraints faced by the stakeholders are high initial investment with a score of 78.8, battery life with a score of 59.2. The suggestions were provided for the major constraints involved in both adopters and non adopters of drones in agriculture.